Pengaruh Pendapatan Asli Daerah, Dana Alokasi Khusus Fisik Dan Dana Desa Terhadap Kemiskinan Aceh 2015-2024 - Abdul Latif; Jean Elikal Marna (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Economic growth is the essential indicator that determining the progress and welfare of a nation, where one measure of progress is to assess the existing poverty rate. Aceh as the one of the provinces in Indonesia with the highest poverty rate, with a massive gap between urban and rural areas. In poverty alleviation, development is needed to stimulate the community to escape poverty and find employment. This study has intended to: (1) gauge the impect of local revenue on poverty in Aceh from 2015 to 2024. (2) To quantify the impect of the Special Allocation Fund on poverty in Aceh from 2015 to 2024. (3) To measure the impact of the Village Fund on poverty in Aceh from 2015 to 2024 and the impect of all independent variables used. This research is quantitative explanation using panel data with data collecting from BPS and Ministry of Finance. The output ilustrate that local revenue and special allocation funds gave a negative and insignificant effect on poverty reduction in Aceh from 2015 to 2024. The village fund variable depicted a negative and significant relationship with poverty reduction in Aceh during the observation period (2015-2024).